New creep at school - Mann, Greyson (Mann, Greyson. Creeper diaries, 2017)
"Gerald is thrilled when a new creeper starts up at Mob Middle School. Finally, there'll be a mob to hang out with that ISN'T a bouncy slime or a flesh-eating zombie! With Connor by his side, Gerald starts his 30-day plan to make creepers the coolest mob at school"--